PENERAPAN PEMBELAJARAN AKTIF TIPE KELOMPOK BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 HILIRAN GUMANTI - Paramita, Winda; Haryono, Yulia; Yuliana Fitri, Dewi (Pendidikan Matematika, 2014)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  ABSTRACTÂ ThisÂ  research was carried out due to the studentsâ low understanding on mathematics concept. This research was designed for revealing whether the mathematics conceptual understanding of the students taught by using Study Group active learning type was better than that of students taught by using conventional learning in class VII of SMPN 1 Hiliran Gumanti. This was an experimental research. Based on the result of data analysis, it was found that the two sample classes were normally distributed and homogenous. In addition, the result of t-test showed that the value of tcalculated (3,82) was higher than ttable (1,645) indicating that the hypothesis was accepted. Hence, it was concluded that he mathematics conceptual understanding of the students taught by using Study Group active learning type was better than that of students taught by using conventional learning in class VII of SMPN 1 Hiliran Gumanti.